The Impact of Using Prior and Acquired Knowledge Strategy on the Achievement and Acquisition of Scientific Concepts for the Third Basic Grade Students in Jordan - AbdelRahman, Fadia Hassan Nimr; Abu Sneineh, Ouda AbdelGawad (Journal of Curriculum and Teaching Methodology, 2023)
The current study aimed to identify the effectiveness of using the previous and acquired knowledge strategy on the achievement of science and the acquisition of scientific concepts among third-grade students in Jordan. The researcher developed an academic achievement test and an acquisition scientific concepts test. Then, the validity and reliability of these instruments were confirmed. The study sample was selected from the third grade students in Al-Muhajireen Basic Mixed School affiliated to the Directorate of Education in Qasaba Amman District. The study adopted the quasi-experimental mode of inquiry. Therefore, two classes were randomly selected from the third grade basic classes; the sample included (40) male and female students. The study revealed superiority in favor of the experimental group that utilized the previous and acquired knowledge strategy in improving the achievement of the general science subject among the third - grade students, compared to using the usual method of teaching. Moreover, The study revealed indicated superiority in favor of the experimental group that adopted the previous and acquired knowledge strategy in acquiring students of the third basic grade of scientific concepts compared to using the usual method of teaching, the The study revealed showed the superiority of the experimental group that used the previous and acquired knowledge strategy in retaining the achievement of general science subject among the students of the third basic grade compared to using the usual method of teaching. In addition, The study revealed showed the superiority of the experimental group that the previous and acquired knowledge strategy in retaining the third grade students' acquisition of scientific concepts compared to using the usual method of teaching.
Keywords: Prior and Acquired Knowledge Strategy; Science Achievement; Acquisition